"The Language We Use Matters": Streams, Narratives, and the Obama Administration Drone Strike Program in Yemen. Issue 3 (8th April 2019) - Ceccoli, Stephen
Abstract : Despite its ubiquity in the literature, John Kingdon's multiple streams framework (MSF) has rarely been applied to defense and foreign policy domains. Moreover, as a rationalist‐based systemic explanation, scholars have generally underappreciated the framework's attention to the role of ideas and policy narratives. Deriving theoretical insights from the narrative policy framework (NPF), this article marries MSF's systemic components with a policy narrative–based explanatory logic to examine decision coupling in the Obama administration's lethal drone strike program in Yemen. Narrative‐specific meanings associated with MSF's systemic features offer both theoretical insight on how the streams interact with respect to the drone program and how policy narratives offer a vehicle for better explaining the manipulation of ambiguity in the policy process. Policy narratives can be seen as cause and effect stories designed to bias certain policy decisions and provide important insights for enriching conventional MSF explanatory mechanisms, including manipulation, decision coupling, and alternative selection.